DETECTION OF CD4+ T-LYMFOCYTE ADAPTIVE IMMUNITY CELL EXPRESSION IN MICE INFECTED WITH Salmonella typhimurium - Mutia Hariani Nurjanah (Jurnal Biosains Pascasarjana, 2022)
Salmonella typhi is a gram-negative, intracellular facultative bacterium that can live and even reproduce in macrophages, resistant to lysosomal enzymes, which has the ability to prevent phagosome-lysosome fusion, making it difficult to kill. stimulates the immune response in the host (Abbas et alll, 2016; Tores et alll, 2000). White turmeric (Curcuma zedoaria) is one of the herbal plants used as an immunomodulator. Immodulators in white turmeric substances function to increase the function of phagocytosis in macrophages to destroy Salmonella typhimurium bacteria. The purpose of this study was to determine the difference between white turmeric extract as an immunomodulator on the number of CD4+ T lymphocytes in BALB/c mice infected with Salmonella typhimurium. This research is a true experimental research with a posttest only control group design. Mice were divided into 5 groups consisting of negative control group, positive control and test group. Analysis of CD4+ lymphocyte data showed a significant difference p=0.013, this indicated that administration of white turmeric extract (Curcuma zedoaria) had an effect on the number of CD4+ T lymphocytes in BALB/c mice infected with Salmonella typhimurium